2002
DOI: 10.1038/sj.hdy.6800027
|View full text |Cite
|
Sign up to set email alerts
|

Developmental stability in Brassica cretica: the effect of crossing distance on fluctuating asymmetry in cotyledon morphology

Abstract: In the present investigation of Brassica cretica, a wild relative of the cultivated cabbage, B. oleracea, we performed an extensive crossing experiment, involving self-pollinations, random outcrosses within populations and hybridizations between populations or species, to evaluate the relationship between crossing distance and developmental stability, estimated as the absolute difference between the right and left lobe of the cotyledons. The frequency distribution of the right-minus-left scores had a narrower … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
18
0

Year Published

2002
2002
2009
2009

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(20 citation statements)
references
References 45 publications
2
18
0
Order By: Relevance
“…Based on the bootstrapping analyses, the frequency distribution of the asymmetry scores for petal length and cotyledon area had a significantly narrower peak than expected for a normal distribution (see also Rao et al 2002). Such leptokurtosis has been observed in several investigations (e.g., Waldmann 1999) and can be attributed to a variety of factors, including allometry and pooling of samples that differ in patterns and amounts of asymmetry (Palmer and Strobeck 1992;Houle 1997).…”
Section: Discussionmentioning
confidence: 85%
See 2 more Smart Citations
“…Based on the bootstrapping analyses, the frequency distribution of the asymmetry scores for petal length and cotyledon area had a significantly narrower peak than expected for a normal distribution (see also Rao et al 2002). Such leptokurtosis has been observed in several investigations (e.g., Waldmann 1999) and can be attributed to a variety of factors, including allometry and pooling of samples that differ in patterns and amounts of asymmetry (Palmer and Strobeck 1992;Houle 1997).…”
Section: Discussionmentioning
confidence: 85%
“…Although the developmental stability of plants has been shown to be influenced by pollution, herbivory, competition, inbreeding, and hybridization (Freeman et al 1993;Kozlov et al 1996;Sherry and Lord 1996a;Møller 1998;Siikamäki and Lammi 1998;Møller and Shykoff 1999;Roy and Stanton 1999;Waldmann 1999;Andalo et al 2000), others have found weak or nonsignificant relationships between stress and fluctuating asymmetry (Fowler and Whitlock 1994;Freeman et al 1995;Sherry and Lord 1996b;Anne et al 1998;Perfectti and Camacho 1999;Wilsey and Saloniemi 1999;Rao et al 2002). As yet, only a few attempts have been made to include more than one population in experimental studies of fluctuating asymmetry (e.g., Waldmann 1999;Rao et al 2002). Thus, it remains to be seen whether stress-related changes in asymmetry are specific to the population in which they have been detected or whether they also apply more generally.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Many of these show that hybridization (outbreeding) or inbreeding effect FA in a highly unpredictable manner and that FA measurements can therefore not be considered a reliable indicator of disturbance in the genetic makeup (Lamb et al, 1990;Rao et al, 2002;Kruuk et al, 2003). However, when fitness traits themselves are investigated, inconsistencies in the effects of inbreeding and outbreeding are also found.…”
Section: Genetic Factors and Extinctionmentioning
confidence: 99%
“…Many studies have demonstrated increased FA (reflecting increased DI) in populations undergoing stress due to both environmental (Ji et al, 2002;Mpho et al, 2002) and genetic factors, such as inbreeding (Waldmann, 1999;Schaefer et al, 2006), but others have failed to find a relationship between FA and environmental (Bjorksten et al, 2001;Kruuk et al, 2003;Sonne et al, 2005) or genetic factors (Fowler and Whitlock, 1994;Rao et al, 2002;Kruuk et al, 2003); consensus regarding the utility of FA as a stress indicator is lacking (Palmer, 1996;Leung et al, 2003).…”
Section: Introductionmentioning
confidence: 99%